Delivery of liquorice extract by liposomes and hyalurosomes to protect the skin against oxidative stress injuries. (10th December 2015) - Castangia, Ines; Caddeo, Carla; Manca, Maria Letizia; Casu, Laura; Latorre, Ana Catalan; Díez-Sales, Octavio; Ruiz-Saurí, Amparo; Bacchetta, Gianluigi; Fadda, Anna Maria; Manconi, Maria
Highlights: Liquorice extract (LQC) was successfully obtained from Glycyrrhiza glabra L. roots. LQC extract was incorporated into conventional and innovative vesicles. LQC loaded vesicles protected fibroblasts against H2 O2 induced oxidative stress. LQC loaded vesicles were able to inhibit the onset of skin damage. Abstract: Liquorice extract, obtained by percolation in ethanol of Glycyrrhiza glabra L. roots, was incorporated in liposomes and hyalurosomes, new phospholipid-sodium hyaluronate vesicles, and their protective effect against oxidative stress skin damages was probed. As a comparison, raw glycyrrhizin was also tested. All the vesicles were small in size (≤100 nm), with a highly negative zeta potential ensuring long-term stability, and able to incorporate a high amount of the extract. In vitro tests showed that the liquorice extract loaded in vesicles was able to scavenge DPPH free radical (80% inhibition) and to protect 3T3 fibroblasts against H2 O2 -induced oxidative stress, restoring the normal conditions. By contrast, glycyrrhizin showed poor antioxidant activity, and was not able to efficiently counteract the oxidative effect of H2 O2 . In addition, the incorporation of the liquorice extract into the vesicular systems promoted the proliferation and migration of 3T3 fibroblasts, favouring the closure of the scratched area. In vivo anti-inflammatory tests on mice confirmed the ability of the proposed nanosystems to improve the local efficacy of the extract, favouring the re-epitelization process.